2018
DOI: 10.1177/2158244018788607
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Norms in Media: Acculturation in Hispanic Children’s Storybooks Compared to Heritage and Mainstream Cultures

Abstract: Cultural artifacts such as children's storybooks may serve to facilitate learning of emotion display norms. We compared emotion displays in European American and Mexican books to infer cultural differences between the mainstream and a heritage culture to ultimately explore acculturation orientation in Hispanic storybooks. Totally, 1,059 images were coded from 10 popular storybooks from each cultural group. We focused on emotion type (positive, negative socially engaging, and disengaging) and intensity of expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Additionally, positive emotions were more frequent than negative powerless and negative powerful emotions (69% vs. 31%) (Vander Wege et al, 2014). Similar results were observed in a study that compared Hispanic, Mexican, and European–American children's storybooks (Sanders, Friedlmeier, & Sanchez Gonzalez, 2018). Another study analyzed the same children's books in English and Japanese and found that both samples contained similar numbers of emotional references and frequencies of emotional terms (Dyer‐Seymour et al, 2004).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, positive emotions were more frequent than negative powerless and negative powerful emotions (69% vs. 31%) (Vander Wege et al, 2014). Similar results were observed in a study that compared Hispanic, Mexican, and European–American children's storybooks (Sanders, Friedlmeier, & Sanchez Gonzalez, 2018). Another study analyzed the same children's books in English and Japanese and found that both samples contained similar numbers of emotional references and frequencies of emotional terms (Dyer‐Seymour et al, 2004).…”
Section: Introductionsupporting
confidence: 86%
“…Regarding differences, children's storybooks from the United States exhibited more positive emotional expressions than those from Romania (Vander Wege et al, 2014) and Taiwan (Tsai et al, 2007), but no differences were found between the storybooks from the United States and Turkey (Vander Wege et al, 2014). Additionally, the Romanian, Turkish, Hispanic, and Mexican books showed significantly higher percentages of negative powerless emotions than negative powerful emotions whereas the U.S. and European–American books displayed both emotions equally (Sanders et al, 2018; Vander Wege et al, 2014). A study that compared the same books published in both English and Japanese found more references to the term surprise in the Japanese versions of the books than in the English versions (Shatz, Dyer, Wellman, Bromirsky, & Hagiwara, 2001 cited by Dyer‐Seymour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using guidelines from previous research (Dyer-Seymour et al, 2004; Sanders et al, 2018), popular American storybooks were selected from Amazon.com in America and Chinese storybooks were selected from JD.com in Mainland China. Both websites provided information on the “Bestseller” status of storybooks and are commonly used websites for buying books in the respective countries.…”
Section: Methodsmentioning
confidence: 99%
“…At least two research gaps are worthy of discussion. First, the majority of extant research on this topic mainly focuses on the pictures or images in children’s storybooks (Grady et al, 2019; Sanders et al, 2018; Tsai et al, 2007; Wege et al, 2014), leaving the narratives or texts that communicate cultural ideals about emotion understudied. To the best of our knowledge, the only study that examines the emotion-related narrative or text of the storybooks has been conducted by Dyer-Seymour et al (2004), who found that no difference in emotional states (e.g., fear, cheer, fun, kiss, and love) in storybooks written in English for American audiences and those written in Japanese for Japanese audiences.…”
Section: Introductionmentioning
confidence: 99%